The perceived impact of the KAM reforms on audit reports, audit quality and auditor work practices: stakeholders' perspectives. Issue 3 (17th May 2021) - Nguyen, Lan Anh; Kend, Michael
Abstract : Purpose: The purpose of this study is to understand how the new reforms related to key audit matters (KAM) disclosures in Australia may have impacted audit quality by eliciting the perceptions of key stakeholders in the audit and assurance services market. Design/methodology/approach: The study uses a qualitative approach and New Institutional Sociology (NIS) to explain how auditors have responded to the KAM reforms. Interviews were conducted with 20 individuals representing identified groups of stakeholders in the market for audit and assurance services in Australia. Findings: The study finds there is little consensus between some stakeholder groups on whether the KAM reforms may have improved audit quality, based on the perceptions shared. The findings conveyed that the auditors and regulators, standard setters acknowledge that KAM disclosures are either costly and/or time-consuming to implement. The Big Four auditors indicate these reforms led to changes mainly around internal consultations and independent reviews, whereas the non-Big Four auditors highlighted increased interactions with audit clients. Originality/value: This is one of the first studies to examine the perceived post-implementation impacts on audit quality of the KAM reforms (ISA 701) after the initial two years of implementation and how auditors have responded, explored through the lens of institutional logic.